Illusionism, Moore, and Chalmers - Loginov, Evgeny V. (Frontiers in Psychology, 2024)
In 1939, G.E. Moore presented his famous proof of an external world. In 2018, David Chalmers published his Moorean argument against illusionism. In 2022, Chalmers argued that Moore's original argument was wrong. In this paper, I will try to defend the original Moore’s argument against Chalmers-style criticism, and show that Chalmers's Moorean argument against illusionism cannot refute illusionism.